To the Conception of Existoencephalic System of Cooled Brain. Part 4. Fractal Morphometry of Trigger Structures of Thermoregulation at Cold Stress - Babijchuk, G. A.; Marchenko, V. S.; Grischenko, V. I.; Babijchuk, V. G. (Problems of Cryobiology and Cryomedicine, 2002)
To estimate structural and functional state of neurohumoral system of cooled brain there has been proposed the method of fractal morphometry using elaborated by the authors computer analysis system FRAM 2000. It was shown that fractal dimensions could be used as an integral index of the activity of various functional systems in an organism. Â 